Essential Roles and Risks of G-Quadruplex Regulation: Recognition Targets of ALS-Linked TDP-43 and FUS - Ishiguro, Akira; Ishihama, Akira (Frontiers in Molecular Biosciences, 2022)
A non-canonical DNA/RNA structure, G-quadruplex (G4), is a unique structure formed by two or more guanine quartets, which associate through Hoogsteen hydrogen bonding leading to form a square planar arrangement. A set of RNA-binding proteins specifically recognize G4 structures and play certain unique physiological roles. These G4-binding proteins form ribonucleoprotein (RNP) through a physicochemical phenomenon called liquid-liquid phase separation (LLPS). G4-containing RNP granules are identified in both prokaryotes and eukaryotes, but extensive studies have been performed in eukaryotes. We have been involved in analyses of the roles of G4-containing RNAs recognized by two G4-RNA-binding proteins, TDP-43 and FUS, which both are the amyotrophic lateral sclerosis (ALS) causative gene products. These RNA-binding proteins play the essential roles in both G4 recognition and LLPS, but they also carry the risk of agglutination. The biological significance of G4-binding proteins is controlled through unique 3D structure of G4, of which the risk of conformational stability is influenced by environmental conditions such as monovalent metals and guanine oxidation.